Effects of lighted incubation and foraging enrichment during rearing on individual fear behavior, corticosterone, and neuroplasticity in laying hen pullets - Saskia Kliphuis; Maëva W.E. Manet; Vivian C. Goerlich; Rebecca E. Nordquist; Hans Vernooij; Frank A.M. Tuyttens; T. Bas Rodenburg (Poultry Science, 2024)
ABSTRACT: Environmental conditions during incubation and rearing can influence stress responsivity of laying hen pullets throughout their lifespan, and therefore have important implications for their welfare. In this study, a 12:12h green LED light-dark cycle during incubation and larvae provisioning as enrichment during rearing were tested as strategies to optimize early-life conditions and thereby decrease stress responsivity in ISA Brown laying hens. A combination of parameters was measured to indicate neuronal, physiological, and behavioral changes that may affect fear and stress. The proteins calbindin D28k (calbindin1), doublecortin (DCX), and neuronal nuclein protein (NeuN) were quantified after hatch as a proxy for brain plasticity. Plasma and feather corticosterone levels were measured after hatch and at the end of the rearing phase, and fearfulness was investigated through a series of behavioral tests (i.e., voluntary approach, open field, tonic immobility, and manual restraint tests). No effects of light during incubation were found on calbindin1, DCX, or NeuN. Neither of the treatments affected corticosterone levels in blood plasma and feathers. Light-incubated pullets showed less fearfulness towards humans in the voluntary approach test, but not in the other behavioral tests reported in this study. Larvae provisioning had no effect on behavior. Our study showed minor effects of light during incubation and no effects of enrichment during rearing on stress responsivity of laying hen pullets. The small effects may be explained by the enriched rearing conditions for all birds in this experiment (low stocking density, natural daylight, and 24/7 classical music). Given the promising results of lighted incubation in other studies, which were mostly performed in broiler chickens, and evidence regarding the positive effects of enrichment during rearing, the potential of these strategies to improve laying hen welfare needs to be explored further.